PERAN MEDIASI CITRA MEREK ANTARA ELECTRONIC WORD OF MOUTH (E-WOM) DAN MINAT BELI KONSUMEN PRODUK KOSMETIK DI TOKOPEDIA - Wella Novianti Novianti; wan laura Hardilawati; Hichmaed Tachta Hinggo S (Fakultas Ekonomi Universitas Kadiri, 2022)
This study aims to determine and analyze the Mediating Role of Brand Image Between Electronic Word Of Mouth (E-Wom) and Consumer Purchase Interest of Cosmetic Products at Tokopedia. This research is a quantitative research with a research sampling method, namely the Nonprobability sampling method. The sample used is 100 who have made a purchase of cosmetics at Tokopedia. The results showed that e-wom had a positive and significant effect on buying interest. The brand image variable has a positive but not significant effect. The results of this study that e-wom has a significant and significant effect on brand image, while the mediation regression test concludes that e-wom mediates brand image on buying interest. These results mean that when consumers get positive information about a cosmetic product from other consumers who have used a product before on the internet. Consumers believe that they choose the right product, so that consumer interest in making purchases is getting bigger.